Conditional essentiality of the 11-subunit complex I-like enzyme in strict anaerobes: the case of Desulfitobacterium hafniense strain DCB-2 - Willemin, Mathilde Stéphanie; Armand, Florence; Hamelin, Romain; Maillard, Julien; Holliger, Christof (Frontiers in Microbiology, 2024)
In oxidative phosphorylation, respiratory complex I serves as entry point in the electron-transport chain for electrons generated in catabolic processes in the form of NADH. An ancestral version of the complex, lacking the NADH-oxidising module, is encoded in a significant number of bacterial genomes. Among them is Desulfitobacterium hafniense, a strict anaerobe capable of conserving energy via organohalide-respiration. This study investigates the role of the complex I-like enzyme in D. hafniense energy metabolism using rotenone as specific complex I inhibitor in different growth conditions. This revealed that the complex I-like enzyme was essential for growth with lactate and pyruvate but not in conditions involving H2 as electron donor. In addition, a previously published proteomic dataset of strain DCB-2 was analysed to reveal the predominance of the complex in the different growth conditions and to identify potential redox partners. This approach revealed seven candidates with expression patterns similar to Nuo homologues suggesting the use of diverse electron sources. Based on these results, we propose a model where the complex I-like enzyme serves as electron entry point into the respiratory chain for substrates delivering electrons within the cytoplasm such as lactate or pyruvate with ferredoxins shuttling electrons to the complex.